The International Tourism Performance Amidst Several Intervention Events: More than 20 Years of Multi Input Intervention Analysis in Bali, Jakarta, and Kepulauan Riau Provinces - Purwa, Taly (UI Scholars Hub, 2020)
As one of the priority sectors in economic development of Indonesia, tourism is expected to be the main key in accelerating economic and social growth, hence reducing poverty. The tourism performance, especially international tourism market, is highly prone to intervention events that can reduce the number of inbound tourists and produce a negative impact on economic development of the destination country. Therefore, anticipating and mitigating various intervention events is necessary to maintain the performance of the tourism sector in Indonesia. This study investigates the magnitude and patterns of impact of several intervention events on the number of international visitor arrivals via the three main ports of entry of Indonesia, i.e. Soekarno-Hatta Airport, Ngurah Rai Airport, and Batam Port. The multi input intervention models were constructed by covering intervention events, i.e. terrorism, disease pandemic, global financial crisis, natural disaster, and government policy, occurring in a relatively long time span, more than two decades, from January 1999 to August 2020. The results show that an intervention event does not always have a significant impact on the number of international visitor arrivals at the three main ports of entry. Generally, all intervention events can lead to a decrease in the number of international visitor arrivals but with different magnitude and pattern, with the biggest and longest impact is caused by COVID-19 pandemic. The direct or non-delayed pattern of impact only appears for terrorism and natural disaster that affect the number of international visitor arrivals via Ngurah Rai Airport.